Exergy analysis of a flat plate solar collector with latent heat storage by phase change material for water heating applications at low temperature - Angie Rincon Ortega; Mauricio Carmona (Journal of Contemporary Urban Affairs, 2017)
An exergy analysis has been performed to determine the potential for useful work in a latent heat storage system with phase change material (PCM) for a flat-plate solar collector. Commercial paraffin wax is used as PCM to store and release energy in the solid-liquid transformation; this material is located in metal containers under the absorber plate on the bottom insulation of the collector. The exergy analysis is performed in outdoor conditions for days of the low, medium and high radiation taken from October 2016 to March 2017 at Barranquilla city (latitude: 10º 59' 16" N, longitude: 74º 47' 20" O, Colombia). The system is evaluated throughout charge and discharge periods. The energy and exergy balance equations based on the first and second law of thermodynamics is formulated and solved for each element of the collector system as well as for the PCM. Results obtained show the energy distribution and energetic destruction for each system component and its variation as a time function. It was observed that the average energy and energetic efficiency are 28.7 %, 13.2 % for of low radiation days. 26.9%, 20.56% for of medium radiation days, and 23.2%, 18.6% for of high radiation days, respectively. Results of the analysis are shown in detail in the present paper.